Design and implementation of fear emotion inducing system based on high-altitude VR interactive scene - Cong Lin; Yang Jinghua; Sun Jicheng; Cheng Shan; Zhang Taihui; Hu Wendong (Dianzi Jishu Yingyong, 2022)
A fear emotion inducing system is designed and implemented based on high-altitude VR interactive scene, which can provide lower limb somatosensory interaction. By the customized carbon structural steel springboard and its double barrel spring unit at the bottom, the system can produce human multi angle stress shaking after walking and trampling, and also can realize the shaking interaction in the virtual high-altitude scene with matched VR tracker. The system has the function modules of interactive display, pedal matching, virtual scene and experiment management, which can automatically store the physiological data of human, spatial position，time information and task performance during the induction process.